Sentiment Analysis on Social Media: A Transformer-Based Approach for Multilingual Data Insights - Nahar, Sunny Suresh; Agnihotri, Prashant Prakashrao (International Journal of Computer Sciences and Engineering, 2025)
This is a study conducted on the perspective of doing the sentiment analysis about the user reviews on the transformer-based social media platforms. The main focus of this model will be multi-linguistic data as the social media platforms release a tremendous amount of user-generated multilingual data. Thus, NLP techniques become the inevitable part of using them since these will help in analysis across the varied linguistic contexts where his sentiments prevail. The transformerbased models, one as Bidirectional Encoder Representations from TransformersBERT and its multi-lingual form, have been demonstrated significant improvements over traditional sentiment analysis methods. This paper includes the issues in the management of mixed-language data from social media and the proposed methodology using transformer models to conduct sentiment classification. This paper is also meant to evaluate the very potential of the transformer-based techniques in enhancing sentiment analysis in several languages and to give insight into how well such models may work in different languages while performing the same tasks.